Evaluation of three glucometers for whole blood glucose measurements at the point of care in preterm or low-birth-weight infants - Hwang, Joon Ho; Sohn, Yong-Hak; Chang, Seong-Sil; Kim, Seung Yeon (Clinical and experimental pediatrics, 2015)
We evaluated three blood glucose self-monitoring for measuring whole blood glucose levels in preterm and low-birth-weight infants. Between December 1, 2012 and March 31, 2013, 230 blood samples were collected from 50 newborns, who weighed, ≤2,300 g or were ≤36 weeks old, in the the neonatal intensive care unit of Eulji University Hospital. Three blood glucose self-monitoring (A: Precision Pcx, Abbott; B: One-Touch Verio, Johnson & Johnson; C: LifeScan SureStep Flexx, Johnson & Johnson) were used for the blood glucose measurements. The results were compared to those obtained using laboratory equipment (D: Advia chemical analyzer, Siemens Healthcare Diagnostics Inc.). The correlation coefficients between laboratory equipment and the three blood glucose self-monitoring (A, B, and C) were found to be 0.888, 0.884, and 0.900, respectively. For glucose levels≤60 mg/dL, the correlation coefficients were 0.674, 0.687, and 0.679, respectively. For glucose levels>60 mg/dL, the correlation coefficients were 0.822, 0.819, and 0.839, respectively. All correlation coefficients were statistically significant. And the values from the blood glucose self-monitoring were not significantly different from the value of the laboratory equipment , after correcting for each device's average value (P>0.05). When using laboratory equipment (blood glucose ≤60 mg/dL), each device had a sensitivity of 0.458, 0.604, and 0.688 and a specificity of 0.995, 0.989, and 0.989, respectively. Significant difference is not found between three blood glucose self-monitoring and laboratory equipment. But correlation between the measured values from blood glucose self-monitoring and laboratory equipment is lower in preterm or low-birth-weight infants than adults.